Pengaruh Konseling Obat Terhadap Pengetahuan dan Sikap Pasien Kolestrol di Rawat Jalan RS Advent Medan - br. Silalahi, Aancel; br. Sembiring, Novitaria; Hanjaya, Hanjaya; Razoki, Razoki; Neswita, Elfia (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Counseling is a practice that is needed by pharmacists because it provides significant benefits to patients. One of the important pharmaceutical services is counseling. Counseling, which comes from the word "advice," refers to the process of giving advice, interacting in discussions, and exchanging opinions. Good understanding and increased compliance will contribute to the achievement of the patient's treatment goals. Based on a study conducted on patients with cholesterol disease at Medan Adventist Hospital, data was obtained prospectively through the use of pretest and posttest questionnaires. The total number of participants analyzed was 50 people. To analyze the data using a simple linear regression method, as well as conduct validity and reliability tests. In addition, the paired t-test and the crosstab chi square test were also applied to evaluate the relationship between the characteristics and the research. Based on the results of the analysis of respondent characteristic data, it is known that there are 32% or 16 male respondents and 68% or 34 female respondents. This shows that the majority of respondents are women.